Concentration-Dependent Decitabine Effects on Primary NK Cells Viability, Phenotype, and Function in the Absence of Obvious NK Cells Proliferation–Original Article - Li, Xiang; Zhang, Min; Cai, Sisi; Wu, Yaohui; You, Yong; Wang, Xianghong; Wang, Li (Frontiers in Pharmacology, 2021)
Acute myeloid leukemia (AML) cells can evade innate immune killing by modulating natural killer (NK) cells receptors and their cognate ligands in tumor cells, thus it may be possible to restore proper expression of immune receptors or ligands with immune sensitive drugs. Decitabine, as a hypomethylation agent, was approved for the treatment of AML and myelodysplastic syndrome. While clinical responses were contributed by epigenetic effects and the induction of cancer cell apoptosis, decitabine also has immune-mediated anti-tumor effects. After exposure to various concentration of decitabine for 24h, the primary NK cells（AML-NK cells） cytotoxicity and receptor expression (NKG2D and NKp46) displayed parabola-shaped response, while U-shaped response was seen in cytokine release(IFN-γ and IL-10), and these effects were regulated by ERK and STAT3 phosphorylation level. Furthermore, AML-NK cells function displayed different response when the competitive MEK and STAT3 inhibitors applied respectively. Thus, we could conclude that the different dose of decitabine makes various effects on AML-NK cells function and receptors expression.